PENERAPAN HUKUM PEMBANGUNAN DALAM E-PROCUREMENT SECARA ELEKTRONIK DI INDONESIA - Andi Kurniawan; Elfrida Ratwati Gultom (Ensiklopedia of Journal, 2023)
The implementation of the national government system is carried out based on the theory of democracy, namely a system of government that is oriented to the community as Indonesian citizens in its implementation objectives. The authorization of authority granted by law as a legal basis reflects how the government structure of Indonesia as a rule of law state. Law will always coexist closely with development activities, including all aspects such as planning and supervision. One aspect of governance that cannot be separated from the daily activities of governance in community activities is the procurement of goods and services in the framework of increasing the resilience of the Indonesian national economy. Along with technological developments, Indonesia has entered a new phase since the start of the Covid-19 pandemic, namely the start of digital transformation. This digital transformation then penetrated as a facilitator and means of assisting the government in implementing its policies, one of which is by creating e-procurement in the procurement system which is carried out online via the internet network. This system was formed with the aim of helping to reduce the number of corruption and collusion that occur in the implementation of policies in the procurement of goods and services so that the procurement of goods and services can run effectively due to the expected process being more transparent than the conventional procurement of goods and services which was carried out previously. However, even though there has been a change in the system, the government still needs to carry out a continuous system evaluation. This is due to the age of the system which is still new so it requires more attention from the government to finalize the system.Keywords: Application, Law, E-Procurement